Reflectivity from electrochemically protected Nb surfaces - Mickova, Irena (Engineering Society of Corrosion, 2015)
Corrosion resistance of fine mechanically polished and electro-polished Nb surfaces were tested by elliposmetric measurements the reflectivity at various angle of incidence. The same measurements were also repeated on electro-polished Nb surface anodic ally oxidized in 1M H2SO4 during 30 s in the potential/voltage range from 0 to 100 V. From the minimum value of measured reflectivity parallel to plane of incidence, the Brewster angle for each investigated sample was determined. The simultaneous measurements of corrosion parameters Brewster angle have shown that the values of Brewster's angle should be used for fast testing the quality of protected metal surfaces.
Keywords: niobium; anodic oxide films; ellipsometry; Brewster's angle